Conflict, civil society, and women's empowerment : insights from the West Bank and the Gaza Strip - Natil, Ibrahim (Emerald points., 2021)
Women in conflict zones face steep challenges, and nowhere is this clearer than in the West Bank and the Gaza Strip, regions that face reduced foreign aid, foreign occupation, violence, instability, ingrained social conservatism and perpetual political crisis. Yet the stereotypical view that women are unable to act politically in the socially conservative contexts of the Middle East is a long way from the truth. Here Ibrahim Natil shines a spotlight on how young Palestinian women work through civil society organizations (CSOs) to improve their communities' and their own resilience and empowerment. He first outlines the impact of CSOs upon peaceful struggle, human rights and community development relief assistance, highlighting how CSOs respond rapidly to the needs of the population by delivering social, health, cultural and educational services to all sectors of society during humanitarian crises. He then asks how empowered Palestinian women contribute to CSO missions and how CSO missions reciprocally contribute to Palestinian women's empowerment. Ultimately, young Palestinian women's engagement with CSOs proves to strengthen cooperation, communication and cross-fertilization between CSO groups, which in turn increases these young women's agency. Conflict, Civil Society, and Women's Empowerment: Insights from the West Bank and the Gaza Strip is a little-known success story, one that makes for required reading for scholars of development, peace studies, conflict resolution and conflict strategy, and which will inspire women's rights activists around the globe.